THE EFFECT DIFFERENCES OF 30-MINUTES VERSUS 60-MINUTES TELE-EXERCISE ON FITNESS LEVEL OF OBESE EMPLOYEES - Mury Kuswari; Rimbawan Rimbawan; Hardinsyah Hardinsyah; Mira Dewi; Nazhif Gifari (Media Gizi Indonesia, 2022)
The ongoing COVID-19 pandemic causes lower physical activity while exercise intensity also decreases. At the same time, the stress level is increasing, causing low physical fitness level. Due to the importance of human health and company cost to increase their employees’ physical fitness level, and with regard to the limited time of office employees, this research aimed to analyze the effect of tele-exercise duration on the fitness level of obese employees. The design of this study was pre-posttest quasi-experimental design. The subjects of this research were male and female obese employees, aged 18-45 years old, from Fast Moving Consumer Goods (FMCG) company in Jakarta, Indonesia. Subjects then were randomly assigned to a 30-minutes exercise session group (n = 20) or 60-minutes exercise session group (n = 19). Statistical analysis included paired t-test and independent t-test to analyze differences between groups. All aspects of fitness analyzed in this study (strength, flexibility, and cardiorespiratory endurance) were increased in both groups significantly (p<0.05). It was shown that 60-minutes exercise sessions improve overall aspects of fitness better than 30-minutes exercise sessions, except for cardiovascular fitness (VO2 Max). Using an independent t-test, there were no significant differences between 30-minute and 60-minute exercise sessions in terms of mean changes (p>0.05). This study showed that tele-exercise, even if it is done in a short period, 30-minute duration, may improve the overall aspect of fitness level significantly for obese employees. Moreover, in this pandemic time, this kind of program is a better alternative than face-to-face, direct exercise intervention.